Effect of Emergency Scenario-Based Training Program on Knowledge, Self-confidence, and Competency of Elderly Caregiver Volunteers in a Rural Thai Community: A Quasi- Experimental Study - Praditporn Pongtriang; Thassanee Soontorn; Jaruwat Sumleepun; Noawarat Chuson; Praneed Songwathana (Shiraz University of Medical Sciences, 2024)
Background: Many older people with comorbidities encounter emergency or life-threatening situations, but the response is often neglected or delayed, resulting in increased morbidity and mortality rates. Community preparedness to reduce the impact of emergency crises on older people is essential. This study aimed to determine the effect of an emergency scenario-based training program (ESBTP) for elderly care on the knowledge, self-confidence, and competency of volunteer caregivers in a rural Thai community.Methods: The one-group pre-post-test, quasi-experimental study, was conducted with a non-randomized research sampling of 40 community healthcare volunteers in Vibhavadi district, Surat Thani, Thailand. The research was conducted between October and December 2021. The ESBTP was based on Bloom's learning theory. The research instrument was a three-part questionnaire measuring knowledge, self-confidence, and competency in geriatric life-threatening surveillance and emergency assistance (GLTSEA) at one, four, and eight weeks of training. Data were analyzed using Bonferroni statistics and repeated measures ANOVA through the software IBM SPSS version 28 with hypothesis testing at P<0.05.Results: The results revealed that at Week 1, Week 4, and Week 8, the volunteers attending the ESBTP demonstrated significantly higher GLTSEA competency (P<0.001). Otherwise, the participants were not significantly different in GLTSEA knowledge (P=0.068) and self-confidence (P= 0.052) after the training.Conclusions: Volunteers' competency increased after ESBTP, but there must be continuity in community training to develop the relevant knowledge, self-confidence, and skills for emergencies.